The impact and realization mechanism of financial inclusion on multidimensional poverty: Evidence from 426 national‐level impoverished counties in China. (16th May 2022) - Liu, Guibo; Gao, Luyang; Wang, Feifei
Abstract : We examine the impact of financial inclusion on multidimensional poverty in impoverished counties. The results show that (1) financial inclusion can directly alleviate the multidimensional poverty, but this effect is heterogeneous between different groups. (2) Agricultural industrialization is the realization mechanism of financial inclusion to alleviate multidimensional poverty. We recommend that financial inclusion not only need to solve the problem of credit exclusion faced by the poor but also need to improve the ability of the poor to convert credit funds into production capital and combine financial inclusion with agricultural industrialization in poverty areas.